Daya Tarik Wisata pada Museum Kepresidenan Republik Indonesia – Balai Kirti Bogor sebagai Sarana Edukasi bagian dari Sejarah Indonesia - Yuniati, Anik (Journal of Social Service and Empowerment, 2025)
ABSTRACT: The visit of seventh-grade students from Jagakarsa State Junior High School, South Jakarta, to the Balai Kirti Presidential Museum of the Republic of Indonesia primarily aimed to provide an educational and engaging learning experience about the history of Indonesian presidents. The museum houses a diverse collection, ranging from presidential uniforms and achievements during office, to profiles of leaders. By visiting the museum, students can directly observe the historical footprint and contributions of presidents to national development. Furthermore, this visit is expected to motivate students to better understand and appreciate Indonesian history and inspire them to become responsible future leaders. This visit can be an effective way to convey historical information and values ​​to the younger generation, so that they can become citizens who care more about their nation's history. Keywords: Balai Kirti Presidential Museum of the Republic of Indonesia, Bogor, Student Visit, History Education, Young Generation, History Education, Role of the President of the Republic of Indonesia. ABSTRAK: Kunjungan Siswa-siswai Kelas 7 (tujuh) SMP Jagakarsa Jakarta Selatan ke Museum Kepresidenan Republik Indonesia Balai Kirti memiliki tujuan utama untuk memberikan edukasi dan pengalaman belajar yang menarik tentang sejarah para Presiden Indonesia. Museum ini menyimpan koleksi beragam, mulai dari seragam kebesaran presiden, prestasi selama menjabat, hingga profil para pemimpin. Dengan mengunjungi museum ini, siswa dapat melihat secara langsung jejak sejarah dan kontribusi para presiden dalam membangun bangsa.  Selain itu, kunjungan ini juga diharapkan dapat memotivasi siswa untuk lebih memahami dan menghargai sejarah Indonesia, serta menginspirasi mereka untuk menjadi pemimpin masa depan yang bertanggung jawab. Kunjungan ini dapat menjadi salah satu cara efektif untuk menyampaikan informasi dan nilai-nilai sejarah kepada generasi muda, sehingga mereka dapat menjadi warga negara yang lebih peduli terhadap sejarah bangsanya. Kunci: Museum Kepresidenan RI Balai Kirti Bogor, Kunjungan Siswa, Edukasi Sejarah, Generasi Muda, Pendidikan Sejarah, Peran Presiden RI.